Cell biology : Proteolytic relay comes to an end - Scheffner, Martin; Whitaker, Noel J. (My University, 2001)
The cellular protein-degrading machinery detects target proteins by the signals they display. One such signal works for artificial test proteins, but only now has a natural equivalent been found.
Keywords: 570